A new species of Characidium Reinhardt (Ostariophysi: Characiformes: Crenuchidae) from headwaters of rio Pacaás Novos, rio Madeira basin, Rondônia, Brazil - Zanata, Angela M.; Ohara, Willian M. (Zootaxa, 2015)
Characidium summus, new species, is described from rio Pacaás Novos, rio Madeira basin, Rondônia, Brazil. The new species is the unique among congeners for completely lacking an adipose fin and having a complete lateral line. Characidium summus can be further distinguished from congeners, including C. vestigipinne that also has a complete lateral line and adipose fin absent, vestigial or reduced by the absence of dark bars or spots on head, body or fins, except for a dark blotch on the rear of the opercle, a narrow midlateral dark stripe, and a dark basicaudal spot. In addition, C. summus possess a vestigial supraorbital and a remarkably small pseutotympanum. The possible mimetic relationship between the new species with Erythrinus erythrinus is discussed.